Phenology study in nursery of five forage shrub species, using rooting products (Revista Sistemas de Producción Agroecológicos, 2015)
This work was developed at the University of the Llanos, Barcelona located km 12 road Puerto López, where five species were planted in the nursery, Megakespasma erytronchlamys, Tithonia diversifolia, Trichanthera gigantea, Hibiscus rosa sinensis and Mussaenda Alicia, rooting systemic, organic and fertilizers that improve gene expression were used, while they accelerate plant phenology, this in order to get bigger and better productions. Composting 60 days of preparation was used with a good percentage of biomass and organic matter as substrate for filling polyethylene bags 25 x 30 cm with a capacity of 1 kg. Moreover a strainer was used to minimize large particles that may interrupt the development of the root. 350 stakes of 40 cm distributed in a complete block design was planted randomly, separated into five groups each species with 70 stakes. Treatments were T0 (control without application of enraizador), T1 (vinegar), T2 (Hormonagro), T3 (aloe vera) and T4 (phosphate rock), assessments are performed at 15, 30. 45, 60. 75, 90 and 105 days, of the following variables: plant height (cm), diameter of the stem of the plant (cm), root weight (g) and number thereof. Tithonia diversifolia growth was higher (P
Keywords: legumes; forage; root development